Chapter Italy and George Gissing: A Geocritical Approach - Gussago, Luigi (Biblioteca di Studi di Filologia Moderna, 2022)
Victorian novelist George Gissing (1857-1903) was a devotee of ancient Roman culture and visited Italy three times between 1888 and 1897. In spite of this admiration, his relationship with Italy was problematic, largely due to personal mishaps. In light of these conflicting views, my essay considers Gissing's portrayals of mostly Southern Italian locations through his fiction, letters, and travelogues. The focus lies here not so much on the narrator but on the narrated space, with Bertrand Westphal's notion of "geocriticism" at its theoretical core. Far from being a utopian haven, Gissing's Italy emerges as a trans-cultural meeting point where the perception of an "interiorised place" can reshape reality, alter horizons, and redefine established values.